Acquired HIV drug resistance among adults living with HIV receiving first-line antiretroviral therapy in Rwanda: A cross-sectional nationally representative survey. Issue 3 (20th May 2022) - Musengimana, Gentille; Tuyishime, Elysee; Kiromera, Athanase; Malamba, Samuel S.; Mulindabigwi, Augustin; Habimana, Madjid R.; Baribwira, Cyprien; Ribakare, Muhayimpundu; Habimana, Savio D.; DeVos, Josh; Mwesigwa, Richard C. N.; Kayirangwa, Eugenie; et al.
Background: We assessed the prevalence of acquired HIV drug resistance (HIVDR) and associated factors among patients receiving first-line antiretroviral therapy (ART) in Rwanda. Methods: This cross-sectional study included 702 patients receiving first-line ART for at least 6 months with last viral load (VL) results ≥1000 copies/mL. Blood plasma samples were subjected to VL testing; specimens with unsuppressed VL were genotyped to identify HIVDR-associated mutations. Data were analysed using STATA/SE. Results: Median time on ART was 86.4 months (interquartile range [IQR], 44.8–130.2 months), and median CD4 count at ART initiation was 311 cells/mm 3 (IQR, 197–484 cells/mm 3 ). Of 414 (68.2%) samples with unsuppressed VL, 378 (88.3%) were genotyped. HIVDR included 347 (90.4%) non-nucleoside reverse transcriptase inhibitor- (NNRTI), 291 (75.5%) nucleoside reverse transcriptase inhibitor- (NRTI) and 13 (3.5%) protease inhibitor (PI) resistance-associated mutations. The most common HIVDR mutations were K65R (22.7%), M184V (15.4%) and D67N (9.8%) for NRTIs and K103N (34.4%) and Y181C/I/V/YC (7%) for NNRTIs. Independent predictors of acquired HIVDR included current ART regimen of zidovudine + lamivudine + nevirapine (adjusted odds ratio [aOR], 3.333 [95% confidence interval (CI): 1.022–10.870]; p = 0.046) for NRTI resistance and current ART regimen of tenofovir + emtricitabine + nevirapine (aOR, 0.148 [95% CI: 0.028–0.779]; p = 0.025), zidovudine + lamivudine + efavirenz (aOR, 0.105 [95% CI: 0.016–0.693]; p = 0.020) and zidovudine + lamivudine + nevirapine (aOR, 0.259 [95% CI: 0.084–0.793]; p = 0.019) for NNRTI resistance. History of ever switching ART regimen was associated with NRTI resistance (aOR, 2.53 [95% CI: 1.198–5.356]; p = 0.016) and NNRTI resistance (aOR, 3.23 [95% CI: 1.435–7.278], p = 0.005). Conclusion: The prevalence of acquired HIV drug resistance (HIVDR) was high among patient failing to re-suppress VL and was associated with current ART regimen and ever switching ART regimen. The findings of this study support the current WHO guidelines recommending that patients on an NNRTI-based regimen should be switched based on a single viral load test and suggests that national HIV VL monitoring of patients receiving ART has prevented long-term treatment failure that would result in the accumulation of TAMs and potential loss of efficacy of all NRTI used in second-line ART as the backbone in combination with either dolutegravir or boosted PIs.